IL-1β Blockade Attenuates Thrombosis in a Neutrophil Extracellular Trap-Dependent Breast Cancer Model - Gomes, Tainá; Várady, Carolina B. S.; Lourenço, André L.; Mizurini, Daniella M.; Rondon, Araci M. R.; Leal, Ana C.; Gonçalves, Barbara S.; Bou-Habib, Dumith Chequer; Medei, Emiliano; Monteiro, Robson Q. (Frontiers in Immunology, 2019)
Cancer patients are at increased risk of developing thrombosis, comorbidity that has been associated with increased neutrophil counts and the formation of neutrophil extracellular traps (NETs). Interleukin-1β (IL-1β) modulates the expression of granulocyte colony-stimulating factor (G-CSF), a cytokine that promotes cancer-associated neutrophilia and NET generation. Herein, we combined a murine breast cancer model with a flow-restriction thrombosis model to evaluate whether the IL-1β blockade could interfere with cancer-associated thrombosis. Mice bearing metastatic 4T1 tumors exhibited high neutrophil counts as well as elevated expression of G-CSF and IL-1β in their tumors. On the other hand, mice bearing nonmetastatic 67NR tumors showed no elevation in neutrophil counts and displayed low expression levels of G-CSF and IL-1β in their tumors. 4T1 tumor-bearing mice but not 67NR tumor-bearing mice exhibited a NET-dependent prothrombotic state. Pharmacological blockade of IL-1 receptor (IL-1R) decreased the primary growth of 4T1 tumors and reduced the systemic levels of myeloperoxidase, cell-free DNA (cfDNA) and G-CSF, without interfering with the neutrophil counts. Most remarkably, the blockade of IL-1R abolished the prothrombotic state observed in 4T1 tumor-bearing mice. Overall, our results demonstrate that IL-1beta might be a feasible target to attenuate cancer-associated thrombosis, particularly in cancer types that rely on increased G-CSF production and involvement of NET formation.